On some covering properties via a- open sets - Waleed Said Ghani, Tamadher; Hatem Hussein, Jalal (Edelweiss Applied Science and Technology, 2024)
In this paper the notion of a-open set used as a tool to introduce certain types of covering properties which is similar to the familiar property of Hurewicz, and prove that we can use a-open sets instead of open sets in the definition of a-compact and a-Hurewicz space and investigated. Some properties and counter examples are given, also the relationship between these spaces was considered.